Compliance, integrity, and prevention in the corporate sector: the collective mindsets of compliance officers in Germany - Pohlmann, Markus; Starystach, Sebastian (Organizational crime, 2023)
Due to increased enforcement of national and international anti-corruption and competition laws, large multinational companies in Germany are under pressure to develop effective compliance management systems (CMS) for preventing, identifying, and prosecuting violations. Against this background, our contribution asks how these changes in the regulatory environment are reflected at the organizational level of compliance departments. It addresses the collective mindsets in use by senior compliance officers in multinational German firms, reconstructing the logic of doing compliance, integrity management, and prevention. The database consists of problem-centered interviews conducted in Germany and the US with high-ranking compliance employees of multinational companies (n = 27). The paper addresses especially the findings for the German senior compliance officers (n = 15). By using the qualitative method of collective mindset analysis, the question of whether integrity and corresponding prevention measures are understood as a symbolic answer to external normative demands or as a rational business strategy is answered. Our findings are that the theories-in-use at compliance departments indicate that there is indeed a mission, a rational strategy behind doing compliance. The mindsets are strongly influenced by a global cultural model of compliance, which can best be described as a rational choice based on organizational behaviorism. This concept of doing compliance became especially the dominant professional mindset of lawyers in that field. As the global mainstreaming has its roots in the American way of doing compliance, against the background of the long arm of the US Sentencing Commission Guidelines and the Department of Justice’s Evaluation Guidelines of Compliance Programs, just little variances in the mindsets are to be detected within the different compliance departments in Germany as well as between compliance mindsets in Germany and the US.
Gesehen am 11.05.2023